Effects of Low-Flow Sevoflurane Anesthesia on Pulmonary Functions in Patients Undergoing Laparoscopic Abdominal Surgery. (20th June 2016) - Doger, Cihan; Kahveci, Kadriye; Ornek, Dilsen; But, Abdulkadir; Aksoy, Mustafa; Gokcinar, Derya; Katar, Didem
Abstract : Objective . The aim of this prospective, randomized study was to investigate the effects of low-flow sevoflurane anesthesia on the pulmonary functions in patients undergoing laparoscopic cholecystectomy. Methods . Sixty American Society of Anesthesiologists (ASA) physical status classes I and II patients scheduled for elective laparoscopic cholecystectomy were included in the study. Patients were randomly allocated to two study groups: high-flow sevoflurane anesthesia group (Group H, n = 30 ) and low-flow sevoflurane anesthesia group (Group L, n = 30 ). The fresh gas flow rate was of 4 L/min in high-flow sevoflurane anesthesia group and 1 L/min in low-flow sevoflurane anesthesia group. Heart rate (HR), mean arterial blood pressure (MABP), peripheral oxygen saturation (SpO2 ), and end-tidal carbon dioxide concentration (ETCO2 ) were recorded. Pulmonary function tests were performed before and 2, 8, and 24 hours after surgery. Results . There was no significant difference between the two groups in terms of HR, MABP, SpO2, and ETCO2 . Pulmonary function test results were similar in both groups at all measurement times. Conclusions . The effects of low-flow sevoflurane anesthesia on pulmonary functions are comparable to high-flow sevoflurane anesthesia in patients undergoing laparoscopic cholecystectomy.